2015
DOI: 10.1097/igc.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study in the Evaluation of Quality of Life After Vulvar Cancer Surgery

Abstract: Less radical surgery showed objectively better QoL results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…When quality of life was evaluated with the FACT-V questionnaire, results were significantly worse for the functional scale and for the edema, complaints, and need for use of compression stockings. Novackova et al observed worse fatigue and lymphedema in patients undergoing full inguinofemoral lymphadenectomy than in those undergoing SLN biopsy [24]. Forner et al found that inguinofemoral lymphadenectomy had a negative impact on sexual function [25].…”
Section: What Is the Relationship Between Findings On Sln And Survival?mentioning
confidence: 97%
“…When quality of life was evaluated with the FACT-V questionnaire, results were significantly worse for the functional scale and for the edema, complaints, and need for use of compression stockings. Novackova et al observed worse fatigue and lymphedema in patients undergoing full inguinofemoral lymphadenectomy than in those undergoing SLN biopsy [24]. Forner et al found that inguinofemoral lymphadenectomy had a negative impact on sexual function [25].…”
Section: What Is the Relationship Between Findings On Sln And Survival?mentioning
confidence: 97%
“…18, 23 Gunther et al 24 found decreased sexual activity in women treated with vulvectomy compared with women treated with WLE (16% vs 43%), whereas 3 other studies assessing changes in sexual activity over time and across surgical methods were not able to detect differences regardless of the questionnaire used (FACT-V, FSFI, EORTC QLQ-CX24; Tables 2 and 3). 20,21,26 Two studies identified significantly decreased desire and arousal, 18 and more problems with dyspareunia and ability to achieve orgasm in VC patients compared with healthy control women 23 using selfdesigned nonvalidated questionnaires (Table 2). Significant deterioration of general SXF over time before and after the treatment in VC patients was reported in 2 studies, assessed by self-designed nonvalidated questionnaire and the general sex life domain of the ePAQ-PF (Tables 2 and 3).…”
Section: Sexual Functionmentioning
confidence: 99%
“…Another publication prospectively looked at the quality of life after inguinal surgery [29] and authors found a clear benefit for a less radical approach.…”
Section: Discussionmentioning
confidence: 99%